Characterization of a fosA3 Carrying IncC–IncN Plasmid From a Multidrug-Resistant ST17 Salmonella Indiana Isolate - Zhang, Li-Juan; Gu, Xi-Xi; Zhang, Jie; Yang, Ling; Lu, Yue-Wei; Fang, Liang-Xing; Jiang, Hong-Xia (Frontiers in Microbiology, 2020)
The aim of this study was to investigate the characteristics of a fosA3 carrying IncC-IncN plasmid from a multidrug-resistant Salmonella isolate HNK130. HNK130 was isolated from a chicken and identified as ST17 Salmonella enterica serovar Indiana and exhibited resistance to 13 antibiotics including the cephalosporins and fosfomycin. S1 nuclease pulsed-field gel electrophoresis and Southern blot assays revealed that HNK130 harbored only one ~180 kb plasmid carrying fosA3 and blaCTX-M-14, which was not transferable via conjugation. We further examined 107 Escherichia coli electro-transformants and identified 3 different plasmid variants; pT-HNK130-1 (69), -2 (15) and -3 (23), in which pT-HNK130-1 seemed to be the same as the plasmid harbored in HNK130. We completely sequenced an example of each of these variants, and all three variants were IncC-IncN multi-incompatible plasmid and showed a mosaic structure. The fosA3 gene was present in all three and bounded by IS26 elements in the same orientation (IS26-322bp-fosA3-1758bp-IS26) that could form a minicircle containing fosA3. The blaCTX-M-14 gene was located within an IS15DI-ΔIS15DI-iroN-IS903B-blaCTX-M-14-ΔISEcp1-IS26 structure separated from the fosA3 gene in pT-HNK130-1, but was adjacent to fosA3 in pT-HNK130-3 in an inverted orientation. Linear comparison of the three variants showed that pT-HNK130-2 and -3 resulted from the sequence deletion and inversion of pT-HNK130-1. Stability tests demonstrated that pT-HNK130-1 and -3 could be stably maintained in the transformants without antibiotic selection but pT-HNK130-2 was unstable. This is the first description of an IncC-IncN hybrid plasmid from an ST17 S. Indiana strain and indicates that this plasmid may further facilitate dissemination of fosfomycin and cephalosporins resistance in Salmonella.